Quaternary carbonate and evaporite sedimentary facies and their ancient analogues a tribute to Douglas James Shearman - Shearman, Douglas James, 1918-2003.; Kendall, Christopher G. St. C.; Alsharhan, A. S.; ebrary, Inc. (Chichester, U.K. : Wiley-Blackwell, 2011)
"This volume commemorates the eclectic research of Douglas James Shearman into evaporites, which was initiated by his studies of the prograding UAE coastal sabkhas or salt flats that incorporate evaporite minerals which displace and replace earlier carbonate sediments. His subsequent proselytization of the study of ancient evaporites in sedimentary sections all over the world led to fundamental advances in our understanding of arid zone carbonate sedimentology. The papers presented here are based on presentations made in Abu Dhabi, UAE 12-14th October 2004 and 7th -8th November 2006. They provide a retrospective from the 1960's and 70's of Holocene evaporites and carbonates, recapturing Shearman's contribution by revisiting the Holocene coastal evaporite and carbonate sediments of the Arabian/Persian Gulf from Abu Dhabi, Qatar, and Oman. The first set of papers considers these sediments from the perspective of their coastal geomorphology, sedimentary character and their geochemistry. Later papers examine the significance of these settings in the ancient geological section world-wide, including examples from the Mesozoic-Cenozoic of the Moroccan Atlantic margin and the Upper Jurassic Arab Formation of the Arabian Gulf"--
pt. 1. Recent carbonate and evaporite sediments -- pt. 2. Geochemistry of recent carbonate and evaporite sediments -- pt. 3. Ancient carbonates and evaporites.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Carbonate rocks -- Persian Gulf Coast (Persian Gulf States); Evaporites -- Persian Gulf Coast (Persian Gulf States); Facies (Geology) -- Persian Gulf Coast (Persian Gulf States); Geology, Stratigraphic -- Quaternary; Electronic books